Recombinant hNeuritin Promotes Structural and Functional Recovery of Sciatic Nerve Injury in Rats - Wang, Haiyan; Li, Xinli; Shan, Liya; Zhu, Jingling; Chen, Rong; Li, Yuan; Yuan, Wumei; Yang, Lei; Huang, Jin (Frontiers in Neuroscience, 2016)
Neuritin is a new neurotropic factor implicated in nervous system development and plasticity. Studies have shown that Neuritin is upregulated in injured nerves, suggesting that it is involved in nerve repair. To test this hypothesis, we investigated whether recombinant human Neuritin could restore nerve structure and function in a rat model of sciatic nerve injury. Neuritin treatment had a dose-dependent effect on functional recovery 4 weeks after injury, as determined by the walking-track test. Similar trends were observed for gastrocnemius muscular strength and nerve conduction velocity. Additionally, sciatic nerve fiber density and organization as well as degree of remyelination were increased, while growth-associated protein 43 and neurofilament 200 expression was upregulated upon treatment with Neuritin. These findings demonstrate that Neuritin stimulates nerve regeneration and functional recovery and thus promotes the repair of injured sciatic nerves.